KONSTRUKSI REALITAS SOSIAL MAKNA TRADISI PERANG AIR (CIAN CUI) BAGI MASYARAKAT DI SELATPANJANG KABUPATEN KEPULAUAN MERANTI - Mira Asmara; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Selatpanjang Kabupaten Kepulauan Meranti has a unique tradition during the Lunar New Year celebration of Water War (cian cui). This tradition is one of the traditions that originated from the moment children play water during Idul Fitri and the celebration of Chinese New Year. By this tradition society continues to be developed so that become a mixed tradition, create harmony between ethnic and have uniqueness that can attract the interest of domestic and foreign tourists. The implementation is carried out 6 (six) days in a row. So it gets the attention of the government by making a festival in Selatpanjang. The purpose of this research is to know the process of externalization, the process of objectification, and the process of internalization of the society of Selatpanjang about meaning the tradition of Water War (Cian Cui).This research uses qualitative method, the subjects of informants selected using purposive technique, which become informant in this research are 11 people that is 4 ethnic Chinese, 4 ethnic Malay, 2 community figure that is ethnic Chinese and Malay, and 1 person from party Department of Tourism Youth and Sports District of Meranti Islands. The data collection techniques used in this study are interviews, observation and documentation. Data analysis techniques by reducing data, collecting data, presenting data, drawing conclusions, and evaluation by using techniques of validity checking data that is the extension of participation and triangulation.The result of this research is the externalization process of ethnic Chinese and Malay society which mean Water War tradition (cian cui) subjectively as a moment of fun, joy together and is a blessing. The objectification process of the community agreement on the ownership of the water war tradition (cian cui) belongs to the community in Selatpanjang which is illustrated by the good interaction of the inter-ethnic group, while the internalization process that takes place is the whole society mingling in the familiar atmosphere and creating inter-ethnic harmony. By the Government of Kepulauan Meranti District make the water war (cian cui) as annual event in the form of Festival every year since 2017 and has entered as one of the event Calendar Of Event Riau 2017.Keyword : Social reality, Water war (cian cui), society